1997
DOI: 10.1093/clinids/24.3.356
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Impact of Community-Based Azithromycin Treatment of Trachoma on Carriage and Resistance of Streptococcus pneumoniae

Abstract: In February 1995, single-dose azithromycin was given to children with trachoma and their household contacts who were children. For children with trachoma, rates of carriage of pneumococci immediately before treatment with azithromycin and 2-3 weeks, 2 months, and 6 months after treatment were 68% (54 of 79), 29% (11 of 38), 78% (29 of 37), and 87% (34 of 39), respectively. The proportion of carriage-positive children with azithromycin-resistant Streptococcus pneumoniae strains was 1 of 54 (1.9%) before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
152
3
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(164 citation statements)
references
References 17 publications
7
152
3
2
Order By: Relevance
“…This phenomenon occurred both in the crèche and in the orphanage facilities in this study, where the spread of two unrelated pneumococcal clones clearly correlated with prior treatment with ␤-lactams. Similar associations were reported by other researchers in relation to macrolides and trimethoprim-sulfamethoxazole (1,19). In this study, these antimicrobial agents were prescribed only occasionally in both centers.…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon occurred both in the crèche and in the orphanage facilities in this study, where the spread of two unrelated pneumococcal clones clearly correlated with prior treatment with ␤-lactams. Similar associations were reported by other researchers in relation to macrolides and trimethoprim-sulfamethoxazole (1,19). In this study, these antimicrobial agents were prescribed only occasionally in both centers.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of azithromycin resistance at the first cross-sectional survey is consistent with previous studies carried out in Australia, Nepal and the United Republic of Tanzania, all of which showed that substantial azithromycin resistance did not develop following a single treatment dose in areas where the baseline prevalence of the carriage of resistant strains was low. [23][24][25] The prevalence of the carriage of azithromycin-resistant pneumococci rose to just over 1% at the second cross-sectional survey. However, at the third survey, there was no significant difference in prevalence between villages that received three annual MDA rounds and those that received one.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies conducted prior to 2001, which were conducted in populations with little exposure to azithromycin, describe temporary increases in the prevalence of antimicrobial drug-resistant Streptococcus pneumoniae carriage in treated children. 20,[25][26][27] No drug-resistant isolates were detected * Adjusted for effects of child's age < 2 years at enrollment, presence of a toilet in the household, and antibiotic treatment of acute lower respiratory illness during follow-up period. Standard errors corrected for clustering.…”
Section: Discussionmentioning
confidence: 99%